Digital technology and HIV, HCV and STI voluntary counselling and testing: good practice example from Croatia - Nemeth Blažić, Tatjana; Bogdanić, Nikolina; Nola, Iskra Alexandra; Kosanović Ličina, Mirjana Lana; Delaš Aždajić, Marija (Central European Journal of Public Health, 2022)
The aim of this paper is to introduce the digitalization process and its effects on better reach of the target population. Progress in the digitalization and e-health tools worldwide enables new opportunities in prevention, diagnostics and treatment for people living with HIV (PLHIV) and people in the risk of HIV infection, hepatitis C (HCV) and other sexually transmitted infections (STIs), especially in the context of the COVID-19 pandemic. The system already used for voluntary counselling and testing (VCT) at the CheckPoint Centre Zagreb run by the non-governmental organization (NGO) Croatian Association for HIV and Viral Hepatitis (CAHIV) was upgraded and adapted (due to the COVID-19 prevention epidemiological measures) and developed for implementation of the pilot project of feasibility and acceptability of home HIV self-testing (HIVST) among men who have sex with men (MSM) in Zagreb. A special feature of the HIVST mobile application enables an innovative approach in collecting clients' test result feedback. This paper presents the method of use digitalization of the VCT and HIVST activities to support and increase availability of screening testing. Described procedures of new technologies application in VCT services and preliminary results of the HIVST pilot project indicate that technology-delivered interventions can contribute and improve access and utilisation of HIV/STI prevention and care services.
Keywords: Sexually Transmitted Diseases; hepatitida C; Hepatitis C; Homosexuality, Male; HIV Infections; Counseling; lidé; Sexual and Gender Minorities; Pilot Projects; homosexualita mužská; pilotní projekty; COVID-19; HIV infekce; pandemie; Humans; sexuálně přenosné nemoci; Digital Technology; Hepacivirus; Male; Croatia; Chorvatsko; sexuální a genderové menšiny; mužské pohlaví; digitální technologie; Pandemics; poradenství